Odpowiedź :
855 : 2= 422,5
169: 2 = 84,5
422,5- 84,5 = 338cm³
422,5+ 84,5= 507cm³
169: 2 = 84,5
422,5- 84,5 = 338cm³
422,5+ 84,5= 507cm³
pojemnik1 - p
pojemnik2 - q
q=p+169
855cm= 2p + 169cm
2p = 686cm
p= 343
wiec wymiaryp = ∛343 = 7cm
q=512
wiec wymiaryq = ∛512= 8cm
pojemnik2 - q
q=p+169
855cm= 2p + 169cm
2p = 686cm
p= 343
wiec wymiaryp = ∛343 = 7cm
q=512
wiec wymiaryq = ∛512= 8cm
855cm³ - 169cm³ = 686cm³
686cm³ : 2 = 343cm³ - Tyle ma jeden pojemnik
343cm³ + 169cm³ = 512cm³ - Tyle ma drugi pojemnik
686cm³ : 2 = 343cm³ - Tyle ma jeden pojemnik
343cm³ + 169cm³ = 512cm³ - Tyle ma drugi pojemnik